If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + -4 = 42 Reorder the terms: -4 + 3t = 42 Solving -4 + 3t = 42 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3t = 42 + 4 Combine like terms: -4 + 4 = 0 0 + 3t = 42 + 4 3t = 42 + 4 Combine like terms: 42 + 4 = 46 3t = 46 Divide each side by '3'. t = 15.33333333 Simplifying t = 15.33333333
| 4(X-3)+8=60 | | 3x+18y+9xy+x+y= | | 4y-3t-y-5t= | | 8x=x+84 | | 7x+8=5x+22 | | 3x^2+30x+100=0 | | X+(1.5x)+(x+33)=180 | | 2(2x+2)=3x+8 | | 6m+21=9m+6 | | .4(.3x-.2)+.6-2=7(.2x+.2)+18 | | -7p+7=-9p+2p | | .33(9x-15)=.5(10x-6) | | 3t+4=42 | | X+(1.5x)+(x+33)=280 | | x^3-0x^2-3x-2=0 | | 6x+7(4-x)=22 | | x^2+10x+2000=0 | | 12X-X^2-20=0 | | 8(k+3)+7k-24=75 | | 6(f-5)+8=2f | | 3y-4+y+22=8y+20-6y | | 7c=2 | | 7+-8+4=5+-2 | | -4x-10x=112 | | .4(.3x-.2)+.6-2=7(.2x+2)+18 | | 97=93-5k+2(k-22) | | -3.7x=74.0 | | 75x^2+80x+20= | | (1-x)*-.119=(.1-x) | | 8x=2x-10 | | 4+(k+1)= | | 18x^2-15x+3= |